2018
DOI: 10.3389/feart.2018.00222
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Glacial Systems: Speciation, Reactivity, Freezing Behavior, and Alteration During Transport

Abstract: A more insightful view of iron in glacial systems requires consideration of iron speciation and mineralogy, the potential for iron minerals to undergo weathering in ice-water environments, the impact of freezing on concentration and speciation, and potential for glacial delivery to undergo alteration during transport into the ocean. A size fractionation approach improves recognition of iron speciation by separating dissolved Fe (<0.2 or <0.45 µm) into soluble Fe (<0.02 µm) and colloidal/nanoparticulate Fe (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 101 publications
6
85
0
Order By: Relevance
“…Bioavailable Fe contributions from terrestrial pyrite oxidation need to be considered when balancing Fe budgets and quantifying total Fe fluxes (Hawkings et al, ; Raiswell, ), but they generally correlate with primary Fe(II) silicate content in glaciogenic dust sources since they are also sourced from bedrock (Raiswell, ; Shoenfelt et al, ). Thus, loss of reactive Fe does not impact the use of Fe(II) silicates as a proxy for bioavailable physically weathered Fe reaching the ocean; Fe in pyrite and on reactive Fe(II) silicate surfaces is readily mobilized and likely becomes bioavailable to phytoplankton (Raiswell et al, ), but a primary Fe(II) silicate signature remains.…”
Section: Resultsmentioning
confidence: 99%
“…Bioavailable Fe contributions from terrestrial pyrite oxidation need to be considered when balancing Fe budgets and quantifying total Fe fluxes (Hawkings et al, ; Raiswell, ), but they generally correlate with primary Fe(II) silicate content in glaciogenic dust sources since they are also sourced from bedrock (Raiswell, ; Shoenfelt et al, ). Thus, loss of reactive Fe does not impact the use of Fe(II) silicates as a proxy for bioavailable physically weathered Fe reaching the ocean; Fe in pyrite and on reactive Fe(II) silicate surfaces is readily mobilized and likely becomes bioavailable to phytoplankton (Raiswell et al, ), but a primary Fe(II) silicate signature remains.…”
Section: Resultsmentioning
confidence: 99%
“…Glacially derived Fe has been distinguished in three forms: truly dissolved Fe (pore size < 0.02 μm), colloidal/nanoparticulate Fe (0.02 to 0.45 μm), and sediment-bound nanoparticulate Fe (>0.45 μm; Statham et al, 2008;Raiswell & Canfield, 2012;Hawkings et al, 2014). Recent studies in the Greenland and Antarctica showed that the largest source of Fe is sediment-bound Fe, while truly dissolved Fe is typically the least abundant phase (Hawkings et al, 2014;Hodson et al, 2017;Raiswell et al, 2018;Statham et al, 2008). Here we present a comprehensive data set of the concentrations and fluxes of filtered Fe (dFe; <0.45 μm) from three Asian glaciers over an entire melt season (Supporting Information S1).…”
Section: 1029/2018gb006113mentioning
confidence: 99%
“…Quantifying the transport of riverine iron (Fe) is critical because it limits the primary productivity in downstream aquatic ecosystems, some of which receive substantial glacier discharge (Martin et al, 1990;Nielsdottir et al, 2009). Ice sheets have recently been shown to deliver large amounts of Fe to coastal ecosystems through outlet glaciers (Hawkings et al, 2014;Hodson et al, 2016Hodson et al, , 2017 and icebergs (Raiswell, 2011;Raiswell et al, 2016Raiswell et al, , 2018. However, Fe release from glaciers distinct from Greenland and Antarctic ice sheets (Hood et al, 2015;Radić et al, 2014) remains poorly constrained at regional and global scales.…”
Section: Introductionmentioning
confidence: 99%
“…Speciation, particle size, surface area, and crystallinity are physical and chemical characteristics of iron minerals that determine if it is available for biological processes. Ascorbate has been shown to selectively extract poorly crystalline, highly reactive Fe(III) 22 , which is potentially bioavailable for phytoplankton 18,23,24 and favorable for microbial reduction 25,26 . Thus, in the context of benthic cycling and early diagenesis, we define ascorbate-extractable Fe(III) as reactive and bioavailable iron (FeR).…”
Section: Introductionmentioning
confidence: 99%